An experimental study on creep of partially molten granulite under high temperature and wet conditions. (15th May 2017) - Zhou, Yongsheng; Zhang, Huiting; Yao, Wenming; Dang, Jiaxiang; He, Changrong
Graphical abstract: Highlights: Natural granulite was experimentally deformed within dislocation creep regime. Creep tests reveal partial melt enhanced weakening at high temperature. Deformation accommodated the nucleation and growth of olivine. Based on creep data, a wet continental lower crust represents a weak layer in the lithosphere. Abstract: Samples of natural granulite were deformed in a gas medium apparatus to evaluate the flow strength of the lower crust. The sample consists of ∼52 vol% plagioclase, ∼40 vol% pyroxene, ∼3 vol% quartz, ∼5 vol% magnetite and ilmenite. Water content was ∼0.17 ± 0.05 wt% in the deformed samples. 40 creep tests were performed on 13 samples at 300 MPa confining pressure, temperatures of 900–1200 °C, and strain rates between 3.13 × 10 −6 and 5 × 10 −5 /s, resulting in axial stresses of 12–764 MPa and the total strain up to 7.8–20.5%. At low temperatures of 900–1000 °C, the microstructural observations show that the granulite samples were deformed in semi-brittle deformation regime, mainly by dislocation glide and intragranular microcracking. At medium temperatures (MT) of 1050–1100 °C, deformation was observed to be dominated by grain boundary migration recrystallization, corresponding to stress exponent nMT of 5.7 ± 0.1, activation energies QMT of 525 ± 34 kJ/mol, log AMT of 1.3. At high temperatures (HT) of 1125–1150 °C, the samples was deformed mainly by grain boundary migration recrystallization accommodated by partial melting and metamorphic reactions characterized by neo-crystallization of fine-grained olivine, with nHT of 4.8 ± 0.1, QHT of 1392 ± 63 kJ/mol, and log AHT of 37.5. Partial melting at high temperatures of 1125–1200 °C, which induces grain boundaries slip and enhances diffusion, has a significant weakening effect on the rheology of granulite, with an estimated strain rate enhancement by 5 times at melt fraction of ∼2 vol%. Reaction from pyroxene to olivine may affect the flow law parameters and deformation mechanism. Based on our data, a wet and cool continental lower crust may still be in brittle deformation regime, whereas a hot lower crust may likely have a weak layer with plastic deformation.